TESTIMONY AT NAS HEARING - STUNT,S (Tufts Archival Research Center, 2007)
Illegible/Difficult to Read; Memorandum from Susan Stuntz to Bob Lewis regarding testimony at the NAS (National Academy of Science) Hearing on aircraft cabin air quality. Lists the four scientists who will testify on behalf of the tobacco industry. Includes predictions as to other organizations’ testimony.